2017
DOI: 10.1007/s11064-016-2171-y
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Ginsenoside Rg1 on Lipopolysaccharide-Induced Cognitive Impairment: Role of Cholinergic System

Abstract: Bacterial endotoxin lipopolysaccharide (LPS) can induce systemic inflammation, and therefore disrupt learning and memory processes. Ginsenoside Rg1, a major bioactive component of ginseng, is shown to greatly improve cognitive function. The present study was designed to further investigate whether administration of ginsenoside Rg1 can ameliorate LPS-induced cognitive impairment in the Y-maze and Morris water maze (MWM) task, and to explore the underlying mechanisms. Results showed that exposure to LPS (500 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Our study has shown that LPS administration significantly increased the IL-6, IL-1β, and TNF-α expression levels in the hippocampus. e expression of TNF-α and IL-1β mRNAs is dynamically regulated by various immune cells in the inflammatory response of the hippocampus [24]. However, QUER has shown the potential to improve abnormalities, such as anxiety-like behaviors, and neuroinflammation by continuously reducing the levels of IL-6 and IL-1β induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that LPS administration significantly increased the IL-6, IL-1β, and TNF-α expression levels in the hippocampus. e expression of TNF-α and IL-1β mRNAs is dynamically regulated by various immune cells in the inflammatory response of the hippocampus [24]. However, QUER has shown the potential to improve abnormalities, such as anxiety-like behaviors, and neuroinflammation by continuously reducing the levels of IL-6 and IL-1β induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it significantly reduced caspase-3 activity, upregulated the expression of PI3K/protein kinase B/glycogen synthase-3β, and downregulated the mRNA expression levels of p21WAF1/CIP1 and p53 in aged rats exposed to isoflurane anesthesia [ 90 ]. It has a protective effect against LPS-induced cognitive deficit and its prevention of LPS-induced changes in the cholinergic system is crucial to this ameliorating effect [ 91 ]. In a dexamethasone-induced cognitive impairment mice model, Rg1 (2 and 4 mg/kg) treatment increased spontaneous motor activity and exploratory behavior in an open field test and increased the number of entries into the new object zone in a novel object recognition test.…”
Section: Pharmacological Potential Of Active Ginseng Constituents In mentioning
confidence: 99%
“…Systemic injection of LPS is associated with neuroinflammation in the hippocampus critical for learning and memory processes [ 9 ], leading to cognitive dysfunction [ 10 ]. Therefore, LPS has been often used to research the biochemical mechanisms of cognitive dysfunction due to inflammation and to develop targeted remedial for neurological symptoms in animal model [ 11 ]. LPS stimulates proinflammatory cytokine cascades by toll-like receptor 4 (TLR4) causing production of many proinflammatory cytokines including IL-6, IL-1 β , and TNF- α , and activation of the nuclear factor-kappaB (NF- κ B) system [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%